STUDI EKSPERIMEN SUPLAI GENERATOR OXYHYDROGEN MENGGUNAKAN KATALIS KOH - Prasetya, Hendrik Elvian Gayuh; Pratilastiarso, Joke; Amalia, Rif'ah; F, Mardatillah Intan (Jurnal Teknologi Terapan, 2019)
Oxyhydrogen  is  the  most  promising  gas  which  significantly  can  reduce  the  fuel consumption  and  the  number  of  emissions  that  produced,  by  adding  the  gas  into combustion  chamber.  To  utilize  decreasing  emissions,  this  paper  study  about  added oxyhydrogens  gas  on  combustion  process  (hybrid)  in  motor  fuel.  This  paper  focuses  on evaluating  the performance  (power, mass  flow, and efficiency)  of oxyhydrogen generator with  12V source  voltage,  while  for  the  generator  installation  circuit  is  done  in  parallel which  is  expected  to  produce  maximum  oxhydrogen  gas  content.  The  type  of  electrolyte used as a generator solution is a base  ????????????  concentrate (1, 3, 5, 7, 9 gram / Li ter), basic solution  ????????????  is  chosen  because  it  has a tendenc to produce a  lot of hydrogen gas.  The methods are design the generator, string the generator and the measuring instrument up, and also the performance testing. As the result, the higher consentrate of the catalyst, the higher the power needed, the higher  mass flow produced, and the higher efficiency that obtained by using parallel electrode aligntment.